Serum oxidative stress level correlates with epicardial adipose tissue thickness in heart failure-reduced ejection fraction patients - Ceyhun, Gokhan; Buyuklu, Mutlu; Topal, Ergun (Annals of Medical Research, 2021)
Aim: In the course of heart failure, various inflammatory cytokines are secreted and oxidative stress occurs. The source of some produced cytokines is epicardial fat tissue (EFT). There is a positive correlation between EFT thickness and metabolic activity. In this study, we aimed to investigate the relationship between oxidative stress and epicardial fat tissue thickness in patients with heart failure.Material and Methods: A total of 36 patients with heart failure-reduced ejection fraction as study group and 36 subjects without heart failure as control group were included in the study. Biochemical blood analyses and echocardiographic examinations were performed.Results: The NT-proBNP level in the heart failure-reduced ejection fraction group was significantly higher than the control group (6506.8±11214.3, 116.5±185.6, respectively, p0.001). The total oxidant status level in the heart failure-reduced ejection fraction group was significantly higher than the control group (14.5±3.7, 10.3±2.0, respectively, p0.001). The total antioxidant capacity level in the heart failure-reduced ejection fraction group was significantly lower than the control group (7.2±2.8, 14.4±8.7, respectively, p0.001). The EFT thickness level in the heart failure-reduced ejection fraction group was significantly higher than the control group (0.78 / (0.67-0.85), 0.51 / (0.37-0.66), respectively, p0.001).Conclusions: Oxidative stress was higher in patients with heart failure and similarly the EFT thickness was found to be increased.